Innovative marketing management strategies: adapting to the digital transformation era - Laili Savitri Noor (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
The advent of digital transformation has revolutionized various aspects of business operations, including marketing management. As businesses increasingly adopt digital technologies, the need for innovative marketing management strategies becomes imperative to stay competitive in the rapidly evolving market landscape. The primary objective of this research is to identify and analyze innovative marketing management strategies that are effective in the digital transformation era. This study adopts a qualitative research approach to explore innovative marketing management strategies in the context of digital transformation. The primary data sources for this study include in-depth interviews with marketing professionals, industry experts, and digital marketing practitioners. Additionally, secondary data sources such as academic journals, industry reports, and case studies are utilized to complement and triangulate the findings from the primary data. Data collection is conducted through semi-structured interviews, allowing for a flexible yet focused exploration of the research topics. The data analysis process involves thematic analysis, which is suitable for identifying, analyzing, and reporting patterns (themes) within qualitative data. In conclusion, the digital transformation era has necessitated significant changes in marketing management strategies. Businesses must integrate advanced digital technologies such as social media, big data analytics, and artificial intelligence to stay competitive. These technologies enable precise targeting, personalized customer interactions, and efficient resource allocation, enhancing overall marketing effectiveness.